Benchmarks for low back pain in general practice in Flanders: electronic audit of INTEGO - Rico Paridaens; Bert Vaes; Steve Van den Bulck; Justine Soetaert (BMC Primary Care)
Abstract Background Low back pain (LBP) is one of the most frequent reasons for encounter in general practice. Yet results from literature show adherence to clinical practice guidelines is low. Audit & feedback is a well-known strategy to improve adherence to guidelines. Benchmarking is an important step in the audit & feedback process. The objective of this study was to develop data-derived benchmarks for low back pain quality indicators. Methods Four electronic health record extractable quality indicators were selected from an existing indicator set developed by CEBAM, an independent, multidisciplinary and interuniversity medical scientific institute in Belgium. Data from 2021-2022 from INTEGO, a general practice morbidity registry, were used to calculate benchmarks for the four quality indicators. The Achievable Benchmark of Care methodology was used to create benchmarks based on the performance of the 10% best-performing practices. Results The following benchmarks were derived: 4.2% prescription for medical imaging, 12.7% prescription for opioids, 27.2% for prescription for non-steroidal anti-inflammatory drugs or acetaminophen, 37.7% prescription for physical therapy and 11.9% prescription for work absenteeism. Conclusions Benchmarks for four electronic health record-extractable quality indicators have been established. They can be used for an electronic audit & feedback tool in primary practice in Flanders or other quality improvement initiatives.